Making it! - Stratford, Bill; Holmes-Lamer, Kim; McLaughlin, Janet; Nelson Davis Television Productions ([Los Angeles, CA ] : Nelson Davis Television Productions, 2005)
Two episodes of the television program Making it! featuring real-life entrepreneurs who share their experiences with marketing small businesses
Title from title screen
Television programs
Executive producer, Nelson Davis
DVD format
Keywords: Marketing -- Management; Small business; New business enterprises